Autotransplantation of mature impacted tooth to a fresh molar socket using a 3D replica and guided bone regeneration: two years retrospective case series - Ye Wu; Jiaming Chen; Fuping Xie; Huanhuan Liu; Gang Niu; Lin Zhou (BMC, 2019)
Abstract Background The aim of this study was to evaluate the clinical outcome of autotransplantation of mature third molars to fresh molar extraction sockets using 3D replicas. Methods Ten patients underwent teeth autotransplantation with or without GBR. We observed the mobility, percussion, radiography examination, the probing depth and the masticatory function of the transplanted teeth during 2 years following up, which were transplanted into fresh molar sockets by using 3D replicas, and GBR when it is necessary. Results The average extra-oral time of donor tooth had been shortened to 1.65 min when used the 3D replica. Some probing depth of the transplanted tooth were deeper than 3 mm at 4 or 5 weeks temporarily. And one patient felt slight sensitive when chewing with soft food at 4 weeks, then disappeared. The clinical examination of the autotransplantation teeth during 1 year follow-up showed no sign of failure. Conclusions The tooth autotransplantation using 3D replica with or without GBR is an effective method which can reduce the extra-oral time of the donor teeth and may result in less failure.